Fischer's mastery of surgery - Fischer, Josef E. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
The scope of Fischer's Mastery of Surgery, Sixth Edition, is consistent with the broad training of a general surgeon, providing extensive coverage of vascular surgery as well as of common thoracic, breast, esophageal, endocrine, colorectal, gastric, pancreatic, liver, and biliary procedures. Each procedural chapter reviews the essentials of diagnosis, anatomy, and pre-operative planning, but focuses most heavily on step-by-step depictions and descriptions of procedures. Each chapter concludes, as is traditional for this classic text, with an editorial commentary which strives to put the chapter in a broad context and provide helpful critiques of the most recent literature. The sixth edition will include a dozen new chapters, including endovascular treatment of varicose veins, fasciotomy, and thoracic aortic transaction. The vascular section has been completely reorganized and will incorporate both open and endovascular procedures. For the first time, the sixth edition is in full color.--Provided by publisher.
Rev. ed. of: Mastery of surgery / editor, Josef E. Fischer ; associate editor, Kirby I. Bland ; section editors, Mark P. Callery ... [et al.]. 5th ed. c2007
Includes bibliographical references and index.
Keywords: Surgical Procedures, Operative